ANALISIS PRODUKTIVITAS TAMBAK SEMI INTENSIF DI PT JATAYU PUTRA DEWATA - Fahrul, Fahrul; Budiman Haruna; Megawati Megawati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the productivity of semi-intensive vaname shrimp farms in PT Jatayu Putra Dewata, focusing on productivity factors, such as operational and financial aspects, fry, feed, medicine, human resources (HR), and technology. Farm productivity was measured through the efficient use of inputs (farm expenditure inputs) and outputs (shrimp yield). The results showed that regular feeding activities tailored to the growth phase of shrimp, the use of quality fry, the role of human resources, as well as the application of technology such as waterwheels and pumps, contributed to productivity in the pond. Operational productivity showed an increase of 07.14% on harvest and 06.45% on fry, while financial productivity increased by 12.93% on harvest and total financial productivity was less than 16.04% on input revenue generated.